Evaluación comparativa técnico-económica y socioambiental de sistemas de levantamiento artificial con respecto al uso de bombas tipo jet en un campo de Geopark (2020)
According to the real information of the operation, the theoretical bases acquired in the Master Program and the additional research, it was possible to carry out the analysis for the change of the artificial lift system of the assigned wells and its comparison with the actual system, where three important aspects were taken into account as they were: Technical, economic and socio-environmental evaluation. This work was structured based on the sequence of the following steps: Gathering of real and theoretical information about the operation, analysis of the current state of the wells, preparation of a qualitative selection matrix, simulation with the Pipesim software of the evaluated wells, evaluation of social and environmental impacts and economic analysis of the project. Finally, the different conclusions and recommendations acquired from the project were proposed so that the operator has the basis to continue with its specific analysis of its application.